Is ‘Tony Cartalucci’ a fictional creation of Eric Draitser and/or Nile Bowie? (The Passionate Attachment, 2014)
By Maidhc Ó Cathail The Passionate Attachment June 12, 2014 Described in his brief bio as “a Bangkok-based geopolitical researcher and writer,” has anyone ever met, spoken to, or even s…